Understanding Impulsive Buying Behaviour Among Buy Now Pay Later (BNPL) Users and its Implication for Overconsumption and The Environment - Verni Juita; Vera Pujani; Rida Rahim; Rita Rahayu (Management Analysis Journal, 2023)
Over the last decade, the popularity of "buy now, pay later" (BNPL) in Indonesia has been increasing due to the various attractive offers available to consumers. However, the unwise use of BNPL may cause impulsive buying behavior, leading to excessive consumptions and waste productions that ultimately negatively affect the environment. Therefore, it is important to understand factors influencing the use of BNPL and impulsive buying behavior in order to help the BNPL users to use it more responsibly, ultimately control their consumption and reduce unnecessary wastes. This study explores the influence of BNPL users' digital financial literacy, self-control, and perceived risk on their impulsive buying behaviors. This study surveys BNPL users in Indonesia through various online channels. Using PLS Smart 3.0 on the survey data of 185 respondents of BNPL users, this study found that digital financial literacy and self-control influenced the impulsive buying behavior of BNPL users. However, the results also show that self-control has a greater influence than digital financial literacy on the impulsive buying behavior of BNPL users. In contrast, risk perception showed the opposite result. Hence, a policy strategy involving self-control and DFL in minimizing impulsive buying should be implemented to avoid overconsumption and waste crises.